儒家誠信倫理乃醫患誠信之本——重塑中國現代醫患信任關係: Confucian Sincerity as the Root of Physician-Patient Trust: Reconstructing a Trust Relation between Physicians and Patients in Contemporary China - YANG, Yang (International Journal of Chinese & Comparative Philosophy of Medicine, 2009)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 針對中國現代社會轉型期的醫患信任危機，本文試從儒家“誠”、“信”的倫理思想出發，揭示儒家誠信思想之本質在於將“誠”作修身之本，以“信”為人倫之道。並通過分析儒家誠信思想側重對人品人格的內在德性的強調，進一步結合傳統社會的醫患交往模式得出傳統社會醫患誠信的特徵是基於醫者篤行“誠信”儒志的人格信任的結論。進而指出儒家誠信思想對改善現代社會轉型期市場經濟衝擊下，醫生逐利失信、患者寓信於利，雙方產生信任危機是具有現實意義的。本文總結出，在社會轉型和醫患關係日趨複雜化的當今，患者弱勢和醫學本質的內在要求從根本上決定了，只有形成一種以醫生為主的道德性信任，即醫生在充分正確認識醫學目的和醫患利益關係後形成作為醫學專業人員的種人生態度和專業精神，進而贏得患者的信任。同時，這種相對穩固的信任關係的形成，也離不開有效的監督機制與合理的制度建設等社會誠信機制的建立。 A crisis of trust exists in the doctor-patient relationship in contemporary transitional China. This essay applies the Confucian notions of sincerity and trustworthiness to analyze the causes of the crisis. It argues that sincerity is the root of trust in human relations. For trust to develop between patients and doctors, sincerity must be cultivated. Without sincerity mediating human relations, trust between doctors and patients is impossible. The Confucian doctrine of sincerity is based on one’s inherent moral personality, and is part of the virtuous treatment of others. In Confucianism, love is a relational virtue, meaning one should practice filial piety, be kind to one’s children, sympathetic to strangers, and so forth; however, one must also be reliable and trustworthy in whatever type of relationship in which one is engaged. To gain the trust of their patients, doctors must demonstrate Confucian virtues in their activities. In addition, with regard to benefits, doctors must not forget virtue or righteousness. They should not make a profit that is not within the scope of Confucian virtue. This point is particularly applicable to today’s crisis of trust, because many consider that doctors have violated Confucian principles by making a profit. The essay concludes that a strong doctor-patient trust relationship cannot be built in contemporary transitional China without the cultivation of the Confucian notion of sincerity. Without doubt, the doctor-patient relationship is complicated by the high-tech medical environment, inevitable vulnerability of patients, and rapid development of the healthcare market. All of these factors make it even more important that doctors form a life attitude that incorporates sincerity and trustworthiness, which are manifested in the virtuous practice of their profession. The Confucian notions of sincerity and trustworthiness will equip doctors to properly understand and achieve professional goals and interests in the care of their patients. Finally, to help in the maintenance of a strong trust relation between doctors and patients, proper public policy, social mechanisms, and effective supervision and regulation based on sincerity and trustworthiness are indispensable. DOWNLOAD HISTORY | This article has been downloaded 340 times in Digital Commons before migrating into this platform.